The Role of Local Wisdom in the Governance of Nunkurus Village - Filmon Mikson Polin (Focus Journal : Law Review, 2024)
This research, entitled "The Role of Local Wisdom in the Governance of Nunkurus Village," addresses the issue of how local wisdom influences the governance of Nunkurus Village. The objective of this study is to ascertain the role of local wisdom in the governance of the village. The research employs an empirical legal study approach, utilizing both primary and secondary data sources. Data collection techniques include document studies and interviews, with data analysis conducted through descriptive qualitative methods. The findings reveal that local wisdom plays a dual role: for the community, it functions as an unwritten rule or law, while for the village government, it acts as a social norm regulating community behavior concerning livestock, and as a sociological/anthropological legal source in the formation of village regulations.